Analisis Alih Kode dan Campur Kode Dalam Tayangan Televisi Emak Enah di Trans 7 - Shofia, Marwa; Supendi, Deden Ahmad; Firdaus, Asep (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This research uses descriptive qualitative analysis with the subject in this research being a program on the Trans 7 channel, namely the program "Enah Makes Enak" which was taken using the listening and recording method with a total of three episodes with a duration of approximately 60 minutes per broadcast. The focus of this research is to analyze code-switching and mixing as well as the factors causing code-switching and code-mixing. Then the data collection technique used in this research is that data collection is carried out using the listening method using note-taking, recording, and data transcription techniques. Another instrument used in this research consisted of hardware in the form of a recording device, namely a cell phone, which was used to record verbal data from the Enah Bikin Enak broadcast. Results and Discussion After analyzing the forms of code-switching and code-mixing, researchers also found several factors in the occurrence of code-switching and code-mixing. In code-mixed speech, two factors were found to cause code-mixing and no factors were found to cause code-switching.